Freedom to Learn Manifesto of Ki Hadjar Dewantara's Educational Philosophy (A new formula in PAI learning) - Akhmad Basuni; Ilzamudin Ma'mur; Ade Fakih Kurniawan (UIN Sunan Gunung Djati Bandung, 2021)
This article discusses the concept of independent learning adopted from the educational philosophy of Ki Hadjar Dewantara. The concept of independent learning in this article is used as a new formula in learning Islamic religious education.This article aims at descriptive-analysis of Ki Hajar Dewantara's educational philosophy in the concept of independent learning as an educational policy in the era of the advanced Indonesian cabinet. It also offers new nuances of Islamic religious education learning methods in schools. The method used is the library research method and is descriptive-analytical in nature, while the analysis uses content-analysis.